Response of Microorganisms to Hot Crude Oil Spills on a Subarctic Taiga Soil - Sparrow, Elena B.; Davenport, Charlotte V.; Gordon, Ronald C. (ARCTIC, 1978)
This study was conducted on the short-term effects of seasonal spills of hot Prudhoe Bay crude oil on microorganisms in a taiga soil in interior Alaska. Following a winter spill, the filamentous fungal populations were inhibited whereas the heterotrophic bacterial populations were stimulated. After a summer spill there was an initial depression of both the filamentous fungal and bacterial populations followed by a general enhancement. In both oil spill plots, yeasts; along with the denitrifying, proteolytic, oil-utilizing, and cellulose-utilizing microorganisms; were favorably affected by the oil. Soil respiration was also enhanced in the oiled plots. An extended period of study is required to fully evaluate the impact of oil on the soil microflora and the role of these microorganisms in recovery of oil-inundated areas in subarctic ecosystems.